Challenges and Strategies in Adapting English Language Teaching Materials : A Study of a Primary School Teacher - Azhar, Mauliya Mizani; Prasetya, Bara Adi; Marwa, Marwa; Annisa, Annisa; Purwanti, Eko (Universitas Muhammadiyah Yogyakarta, 2025)
This study investigates the difficulties and methods primary school teachers have when modifying English language teaching (ELT) resources for use in environments where English is a foreign language (EFL). The two main questions that guide the research are: (1) What difficulties do EFL teachers in elementary schools have when modifying ELT materials to suit the needs of their students? and (2) How do they modify and assess these resources for use in the classroom? Data were collected through semi-structured interviews with chosen English teachers in primary schools were used to gather data. The results were analyzed using thematic analysis. The study identified a number of persistent issues, such as the curriculum's divergence with students' real language skills, the textbooks' inflexible structure, the lack of cultural relevance, and the scarcity of resources. To overcome these obstacles, educators reported using a variety of tactics, including making texts simpler, introducing examples that are culturally relevant, integrating multimedia materials, adapting activities to students' skill levels, and assessing the effectiveness of the materials through informal feedback or classroom assessments. The results point to the necessity of supporting teacher-led content adaptation and allowing for more flexibility in curriculum design. The study highlights the value of teacher creativity in creating engaging and responsive resources for young learners and adds to the expanding conversation on localized ELT approaches.